A note on a polynomial set generated by G(2xt-t2) for the choice G(u)= oF1(--; a; u) - Ahmad Khan, Mumtaz (Pontificia Universidad Católica del Perú, 2014)
The present paper is a study of a class of polynomial set defined by means of a generating function of the form G(2xt- t²) for the choice G(u) = 0 F1(--;α;u). The paper contains some interesting results in the form of recurrence relations, generating functions, finite series of product of polynomials, hypergeometric form, relationship with Shively 's pseudo Laguerre and other polynomials, integral representation, fractional integral and Laplace transform of the polynomial.